The Cambridge aerospace dictionary - Gunston, Bill (Cambridge University Press, 2004)
'The Cambridge Aerospace Dictionary' offers coverage of terminology used throughout the aerospace industry, including materials & aerospace organizations. This new dictionary includes over 15,000 new terms, mostly acronyms.
Updated and enlarged ed. of: Jane's aerospace dictionary / Bill Gunston. New ed., 2nd ed. 1986.
Keywords: Aerospace engineering -- Dictionaries.; Aeronautics -- Dictionaries.; Astronautics -- Dictionaries.; elektronické knihy; electronic books